Inspirasi SUARA UMP III lauches 4 books - Safriza, Baharuddin (2020)
PEKAN, 28 October 2020 – The Office of SUARA Universiti Malaysia Pahang (UMP) has published four new books entitled Kembara PhD, Reinforced Concrete Design, Fires and Explosions – Managing Process Safety, and Capstone Project – Guideline for Undergraduate Civil Engineering Courses.